“Poscolonial Moment” in Foreign Policy Discourse: the Casus of “Global Britain” - K. A. Godovanyuk (Международная аналитика, 2023)
The article explores interrelation between the postcolonial discourse and modern British foreign policy, designated as a “postcolonial moment” in the strategic thinking of the political establishment. It is noted that the withdrawal from the EU has again attracted public and academic attention to the imperial past, which is sometimes regarded not only as a possible reason for Brexit, but also as a starting point for design of the country’s foreign policy under the new conditions (the idea of “Global Britain”). The post-imperial discourse in the modern British political environment is analyzed within several aspects: how it aﬀects the strategic reasoning of the elite circles, speciﬁc trends in dealing with the former colonies, and postcolonialism components in the new foreign strategy (case of “Indo-Paciﬁc tilt”). Proceeding from the paradigm of postcolonial constructivism, the article shows that the issues of imperial heritage still remain an important aspect in British foreign policy identity, but in the context of strategic planning it takes on new meanings. Firstly, the political establishment continues to search for a new international role and appeals to the former colonies as a resource of their foreign policy (whether it is economy, strategy, or image). Secondly, distancing themselves from the rhetoric of the colonial past, they refer to “common history” and identity as the world politics see the formation of a polycentric system. This trend is reﬂected in the challenge of building new long-term alliances through “patient diplomacy.” The “Global Britain” discourse, due to its direct connotation with the postcolonial past, becomes undesirable for both the ruling political elite and the opposition.